Evaluation of the International Study Group of Pancreatic Surgery definition of delayed gastric emptying after pancreatoduodenectomy in a high-volume centre - Welsch, Thilo; Borm, Eva-Mareike; Degrate, Luca; Hinz, Ulf; Büchler, Markus W.; Wente, Moritz N. (The British journal of surgery, 2010)
Delayed gastric emptying (DGE) is a common complication after pancreatoduodenectomy. The International Study Group of Pancreatic Surgery (ISGPS) definition of DGE has not been evaluated and validated in a high-volume centre.Complete data sets including assessment of gastric emptying were identified from a database of patients undergoing pancreatoduodenectomy between 2001 and 2008. Factors associated with DGE (grades A, B and C) were assessed by univariable and multivariable analyses.DGE occurred in 340 (44·5 per cent) of 764 patients. Median hospital stay was significantly prolonged in patients with DGE: 13, 21 and 40 days for grades A, B and C respectively versus 11 days for patients without DGE. DGE was associated with prolonged intensive care unit (ICU) admission (at least 2 days): 20·6, 28·6 and 61·8 per cent of those with grades A, B and C respectively versus 9·4 per cent of patients without DGE. Factors independently influencing DGE grade A were female sex, preoperative heart failure and major complications (grade III-V). Validation of the DGE definition revealed that DGE grades A and B were associated with interventional treatment in 20·1 and 44·4 per cent of patients.The ISGPS DGE definition is feasible and applicable in patients with an uneventful postoperative course. Major postoperative complications and ICU treatment, however, might limit its usefulness. The identified risk factors for DGE are not amenable to perioperative improvement.
Published: 28 April 2010
Gesehen am 23.10.2023